2013
DOI: 10.1128/genomea.00803-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Pasteurella multocida A:3 Strain 671/90

Abstract: Pasteurella multocida serogroup A is commonly isolated from nasal swabs of clinically healthy calves and also from diseased lung tissue in bovine pneumonia. Here, we report the draft genome sequence of the virulent strain P. multocida 671/90, which has been characterized previously in experimental infections of calves and mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…On the other hand occurrence of the factors in apparently healthy lungs could possibly indicate early infection or contained infection which couldn't lead to disease. It was previously reported that this facultative anaerobic bacterium is commonly found in clinically healthy calves (Lainson et al, 2013 ).…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand occurrence of the factors in apparently healthy lungs could possibly indicate early infection or contained infection which couldn't lead to disease. It was previously reported that this facultative anaerobic bacterium is commonly found in clinically healthy calves (Lainson et al, 2013 ).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, our results are in agreement with those previously documents (Adler et al, 1999 ; Wilson and Ho, 2013 ). It has been noted that P. multocida Carter: Heddleston serotype B: 2 strains are commonly responsible for bovine haemorrhagic septicaemia while serovar A: 3 strains are associated with bovine respiratory diseases (Welsh et al, 2004 ; Dey et al, 2007 ; Shivachandra et al, 2011 ; Lainson et al, 2013 ; Wilson and Ho, 2013 ). Both haemorrhagic septicaemia and respiratory diseases including pneumonia are the common infections associated with P. multocida in bovine species (bovine pasteurellosis) (Wilson and Ho, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isolate 619/90 was passaged through another calf to confirm its virulence and generated a new pathogenic isolate, 671/90 ( 3 ). Here, we report the genome sequences of strains 618/90 and 619/90, four of the five field isolates (one was not available), and resequencing of 671/90 ( 4 ), using Illumina short-read and Oxford Nanopore Technologies long-read sequencing to produce single-contig de novo genome assemblies.…”
Section: Announcementmentioning
confidence: 99%